Systematic Analyses of Antigen-Antibody Interactions in vitro: Insights from Three Different Ways of Virus Inactivation and Their Specific Reaction Lines - Bitsch, Viggo (Contemporary Research and Perspectives in Biological Science Vol. 8, 2025)
Antibodies neutralize viruses in three different ways. In contrast to what is commonly perceived, very sensitive and specific tests demonstrating antigens and antibodies can be elaborated on basis of the regular reaction lines demonstrated. The action of the non-neutralizing antibodies is of the greatest importance in combatting and preventing infections. This analytical review aims to clarify the complex lines of antigen-antibody interactions in vitro, to achieve a better understanding of the impact of various antibodies and the reaction lines on the basis of which sensitive and standardized tests for demonstrating antigen and antibody can be elaborated. A variety of aspects of the antigen-antibody binding reactions are evaluated, including 1) the reactions in a conventional neutralization test, 2) the first-order antigen-antibody reaction demonstrated, 3) the formula for the regular reaction without aggregations presenting the log antibody/log virus equivalence factor of neutralization, 4) the lines of two different aggregation reactions inactivating viruses, 5) irreversibility of antigen-antibody bindings, 6) lines for elaborating gold and reference standard assays and highly sensitive routine tests, 7) a “persistent fraction of virus”, and 8) the “Percentage Law”. A series of important conclusions are presented. Antibodies are bound firmly and irreversibly to their antigenic determinants on a virus. The binding reaction does not lead to an equilibrium state as commonly perceived. The sensitivity of antigen-antibody tests may consequently be both variable and adjustable to high levels. Antibodies neutralize viruses in three clearly distinct ways. Neutralization of virus by antibody in a virus-antibody mixture without presence of the complement component C1q proceeds as two separate reactions, i.e., 1) a first-order reaction caused by particularly neutralizing antibodies being bound monovalently to their antigenic neutralization determinant and 2) an early “over-neutralization” reaction that can be attributed to the formation of virus aggregates created by the di- and polyvalent antibodies which to a wide extent are non-neutralizing. This aggregation is caused by the various antibodies, in a synergistic action. It is highly dependent on a sufficient antibody concentration and is prompt and short-lasting. In the serial dilutions of a conventional neutralization test, an early aggregation is readily diluted away with increasing reaction periods. In contrast, the first-order neutralization reaction is slowly progressing but enduring. The test sensitivity, cf. Definitions will be directly proportional to the reaction time but temperature-dependent. The third neutralization reaction is dependent on the presence of a complement. The hexa-valent C1q component will enhance the neutralizing effect of antibodies by aggregating virions that have been bound to a non-neutralizing antibody. Such an antibody is sensitized for binding to the C1q component by being bound to its antigenic determinant on the virion. In a complement-enriched neutralization test, two different reaction rates will be observed. Practically instantly, C1q will react with all pre-formed virus-antibody complexes and, because of the multi-valency of that molecule, include them in aggregates but thereafter, with increasing reaction time, the reaction will be of first-order following the continuous first-order binding of non-neutralizing- antibodies to their antigenic determinants. In a herpesviruses complement-enriched neutralization test, the reaction with non-neutralizing IgG antibodies increased titers recorded for neutralizing IgG antibodies in a conventional neutralization test by a factor of approx. 8, but for IgM antibodies the neutralizing effect by complement was enormous. A significant neutralizing effect could be demonstrated in blood as early as 4 days after experimental nasal infection and after 8 to 15 days, the neutralizing effect was demonstrated in serum diluted 1:10.000 or more. The huge neutralizing potential of the non-neutralizing antibodies in a joint action with complement indicates a fundamental role of these antibodies in combatting infections. The so-called Percentage Law. according to which the rate of virus neutralization will be independent of the virus concentration was found invalid. The formula for the regular lines of antigen-antibody interactions in vitro not comprising aggregation has been presented earlier. Highly sensitive antigen-antibody tests, elaborated on basis of the reaction lines documented, have been in use for a long time in the veterinary medical field.